THE EFFECT OF ATMOSPHERIC SETTINGS: VISUAL STRUGGLES IN THE PLAYS BEYOND THE HORIZON AND ANNA CHRISTIE - Choubey, Rity; Agrawal, Shuchi; Yadav, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The paper explores the relationship between the visualized struggles endured by characters in Eugene O’Neill’s plays and the natural and manmade settings of the Plays. Imtiaz Ali brought to light his writing process in a podcast, unabashedly proclaiming that his popular scenes arise simply from an image or impression of a feeling. Shahryar (2026). Eugene O’Neill’s plays are a depiction of the tragedy that ensues from the physical and psychological sufferings endured by the characters. In plays like Anna Christie and Beyond the Horizon, the geography of the inhabitants plays an integral role in shaping their lives. On the one hand, Christopherson is shown to display a habit of blaming the sea for everything that has made his life miserable; on the other hand, Robert Mayo suffers from an inevitable end after having chosen a farm life that goes beyond his natural disposition, which eventually becomes the cause of his failure in life. Eugene O’Neill’s work has been well established in the drama of topographical representation, articulating the valuation of spaces in dramatic arts. The current study examines the visual representation of the inner and outer experiences of the characters on stage in Eugene O’Neill’s plays Beyond the Horizon and Anna Christie. The study uncovers how ecological and spatial structures shape the psychological condition of the characters depicted in the plays Beyond the Horizon and Anna Christie. A close textual analysis has been performed to understand the impact of atmospheric settings on the spectacle of the plays.